Behavior of calendar anomalies and the adaptive market hypothesis: evidence from the Baltic stock markets. Issue 2 (3rd April 2022) - Aleknevičienė, Vilija; Klasauskaitė, Vaida; Aleknevičiūtė, Eglė
ABSTRACT: This research tests the Adaptive Market Hypothesis (AMH) regarding calendar anomalies in the Baltic stock markets. Analysis of known calendar anomalies over time is carried out by using sub-sample GARCH (1, 1) regression with Kruskal–Wallis statistics and rolling windows. Three calendar anomalies were confirmed in these markets: Friday, MoY (July and January), and ToM (turn-of-the-month). The Baltic stock markets demonstrated behavior supporting the AMH. It was found that the opportunity to earn abnormal returns on investment strategies based on Friday, July, and ToM effects disappeared during the financial crisis of 2007–9. The Friday and the ToM effects follow a more time-varying pattern, while the July effect is less so.